Creating a balanced family travel experience: A perspective from the motivation-activities-transformative learning chain. (January 2022) - Fu, Xiao; Liu, Xinyi; Li, Huiru; Wang, Yanqin; Li, Zhiyong
Abstract: Recreational vehicle (RV) travel is an emerging phenomenon among Chinese families, as RVs integrate daily leisure with long-distance travel. This study applied the constructivist grounded theory approach and analysed 25 interview transcripts and 7 travel posts. Adopting the perspective of the motivation-activity-transformative learning chain, the present research investigated and summarized pretravel motivations, activities undertaken during travel and posttravel transformative learning following a time series and built a holistic and causal framework of the transformational process underlying Chinese families' outbound RV travel. Segments from interviews and travel posts were used to illustrate the themes. This study identified the unique symbolism of the emotional value of the RV for Chinese families and revealed the new tendency for Chinese families to seek out demand-coordinated family leisure experiences. Theoretical and managerial implications for exploring Chinese family tourism and developing this emerging RV market are discussed. Highlights: A motivation-activity-transformative learning chain was formulated in Chinese families' outbound RV travel. The RV concept mainly manifested its sentimental value in Chinese families' travel experiences. Family tourism transformative learning ranges from personal and family dimensions. Chinese parents gradually pursue a balance between their own relaxation and their children's play during family trips.